High-recording-density magnetic medium based on exchange coupling and preparation method thereof
By adding a soft magnetic layer above and below the magnetic recording layer, the coupling strength between soft magnetic particles and hard magnetic particles is optimized, and the exchange coupling effect is used to solve the problems of traditional magnetic recording media in terms of storage density and signal crosstalk, achieving higher Storage density and data reliability.
Patent Information
- Application Number
- CN202411372878.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional coated magnetic recording media have bottlenecks in improving storage density, read and write speed and data reliability, especially the superparamagnetic effect and signal crosstalk problems caused by the reduction of magnetic particle size, which is difficult to be effective while maintaining cost-effectiveness. solve.
Using a high-recording density magnetic medium based on exchange coupling, the coupling strength between soft magnetic particles and hard magnetic particles is optimized by adding soft magnetic layers above and below the magnetic recording layer, the coupling effect is used to reduce the inversion field demand and improve signal-to-noise Compare.
It realizes reducing coercive force and improving thermal stability, improving signal-to-noise ratio, and improving data storage reliability and storage density.
Abstract
Description
Technical Field
[0001] The invention relates to the field of magnetic recording materials, and in particular to a high recording density magnetic medium based on exchange coupling and a preparation method thereof. Background Art
[0002] Coated magnetic recording media, as an important part of the data storage field, has been at the core of information storage technology since the mid-20th century. This type of media forms a magnetic recording layer by evenly coating a coating containing magnetic particles on a non-magnetic substrate, thereby realizing magnetic recording and reading of data. Traditional coated magnetic recording media mainly use ferrite or metal magnetic powder, such as γ-Fe2O3, Co-Fe3O4, Fe-Co alloy, etc. These materials are widely used in floppy disks, magnetic tapes and early hard disk drives due to their good magnetic properties and relatively low cost.
[0003] However, with the rapid development of information technology, the demand for data storage density continues to increase, and traditional coated magnetic recording media are facing a bottleneck in increasing storage density. The main challenges include the superparamagnetic effect caused by the reduction in magnetic particle size, the interaction between magnetic particles, and the resulting signal crosstalk, which limit the reliable storage and reading of data. In addition, in order to achieve high-speed data transmission, the signal response time of the medium needs to be shortened, which requires the magnetic particles to have high coercivity and magnetic anisotropy to ensure the stability and long-term preservation of data.
[0004] In recent years, in order to break through these limitations, researchers have been committed to developing new coated magnetic recording media materials. This includes but is not limited to exploring magnetic materials with higher magnetic anisotropy and coercivity, and optimizing the size, shape and distribution of magnetic particles to reduce interactions between particles. At the same time, new adhesive resins have also been developed to improve the distribution uniformity and stability of magnetic particles on the substrate, further improving the reliability of the media.
[0005] In addition, innovation in coating processes is also key to improving the performance of coated magnetic recording media. For example, the use of precision coating techniques such as slit coating, dip coating, and inkjet printing can achieve finer coating control, which helps to form a more uniform and dense magnetic recording layer. In addition, by improving the drying and curing process, the microstructure of the coating can be effectively controlled, thereby improving the wear resistance and durability of the magnetic recording medium.
[0006] Despite the many advances, how to further improve the storage density, read / write speed and data reliability of coated magnetic recording media while maintaining cost-effectiveness remains a key issue that needs to be solved in this field. Therefore, the development of new coated magnetic recording media materials and preparation methods is of great significance to promoting the advancement of information storage technology. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a high recording density magnetic medium based on exchange coupling and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: In a first aspect of the present invention, a high recording density magnetic medium based on exchange coupling is provided, comprising a first soft magnetic layer, a hard magnetic layer, a second soft magnetic layer, a non-magnetic support body and a back coating layer which are stacked in sequence;
[0009] The raw materials for preparing the first soft magnetic layer include, by weight: 50-150 parts of soft magnetic particles, 15-80 parts of adhesive resin, 2-15 parts of abrasive, 1-10 parts of curing agent, 1-10 parts of lubricant, 1-10 parts of conductive agent, and 125-500 parts of solvent.
[0010] Preferably, the raw materials for preparing the hard magnetic layer include, by weight: 50-150 parts of hard magnetic particles, 30-80 parts of adhesive resin, 2-15 parts of abrasive, 1-10 parts of curing agent, 1-5 parts of lubricant, 1-10 parts of conductive agent, and 150-600 parts of solvent.
[0011] Preferably, the raw materials for preparing the second soft magnetic layer include, by weight: 50-150 parts of soft magnetic particles, 15-80 parts of adhesive resin, 2-15 parts of abrasive, 1-10 parts of curing agent, 1-10 parts of lubricant, 1-10 parts of conductive agent, and 125-500 parts of solvent.
[0012] Preferably, the raw materials for preparing the back coating layer include, by weight: 30-80 parts of adhesive resin, 1-10 parts of curing agent, 1-10 parts of lubricant, 1-10 parts of conductive agent, and 50-150 parts of solvent.
[0013] Preferably, the soft magnetic particles are selected from at least one of α-alumina, β-alumina, γ-alumina, θ-alumina, silicon dioxide, silicon carbide, chromium oxide, cerium oxide, α-iron oxide, goethite, corundum, silicon nitride, titanium carbide, titanium dioxide, tin oxide, magnesium oxide, tungsten oxide, zirconium oxide, boron nitride, zinc oxide, calcium carbonate, calcium sulfate, barium sulfate or molybdenum disulfide.
[0014] Preferably, the hard magnetic particles are selected from at least one of the following materials:
[0015] Metals: Fe, Co, Ni, Alloys: Fe-Co, Fe-Ni, Fe-Al, Fe-Ni-Al, Fe-Al-P, Fe-Ni-Si-Al, Fe-Ni-Si-Al-Mn, Fe-Mn-Zn, Fe-Ni-Zn, Co-Ni, Co-P, Fe-Co-Ni, Fe-Co-Ni-Cr, Fe-Co-Ni-P, Fe-Co-B, Fe-Co-Cr-B, Mn-Bi, Mn-Al, Fe-Co-V, γ-Fe2O3, Fe3O4, Metal compounds: iron nitride, iron carbide, barium ferrite, strontium ferrite, calcium ferrite or lead ferrite.
[0016] Preferably, the adhesive resin is selected from at least one of polyvinyl chloride, polyvinyl acetate, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinylidene chloride copolymer, vinyl chloride-acrylonitrile copolymer, acrylate-acrylonitrile copolymer, acrylate-vinyl chloride-vinylidene chloride copolymer, vinyl chloride-acrylonitrile copolymer, acrylate-acrylonitrile copolymer, acrylate-vinylidene chloride copolymer, methacrylate-vinylidene chloride copolymer, methacrylate-vinyl chloride copolymer, methacrylate-ethylene copolymer, polyvinyl fluoride, vinylidene chloride-acrylonitrile copolymer, acrylonitrile-butadiene copolymer, polyamide resin, polyvinyl butyral, cellulose acetate butyrate, cellulose diacetate, cellulose triacetate, cellulose propionate, nitrocellulose, styrene-butadiene copolymer, polyurethane resin, polyester resin, amino resin or synthetic rubber.
[0017] Preferably, the abrasive is selected from at least one of α-aluminum oxide, β-aluminum oxide, silicon carbide, chromium oxide, cerium oxide, α-iron oxide, corundum, diamond, silica rock, garnet, silicon nitride, boron nitride, molybdenum carbide, boron carbide, tungsten carbide or titanium dioxide.
[0018] Preferably, the curing agent is selected from at least one of toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, naphthylene-1,5-diisocyanate, o-toluidine diisocyanate, isophorone diisocyanate and triphenylmethane triisocyanate.
[0019] Preferably, the lubricant is selected from at least one of silicone oil, fatty acid-modified silicone oil, fluorinated silicone and other fluorinated lubricants, polyolefins, polyethylene glycol, alkyl phosphates and metal salts thereof, polyphenylene ether, fluorinated alkyl ether, lauric acid, myristic acid, palmitic acid, stearic acid, isostearic acid, arachidic acid, oleic acid, eicosanoic acid, elaidic acid, behenic acid, linoleic acid, linolenic acid, octyl stearate, isooctyl stearate, octyl myristate, isooctyl myristate, butoxyethyl stearate, butyl stearate or heptyl stearate.
[0020] Preferably, the conductive agent is selected from at least one of carbon black, acetylene black, carbon fiber, graphene or carbon nanotube.
[0021] Preferably, the solvent is selected from ether solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methanol, ethanol, propanol, methyl acetate, ethyl acetate, butyl acetate, propyl acetate, ethyl lactate, ethylene glycol acetate, diethylene glycol dimethyl ether, 2-ethoxyethanol, tetrahydrofuran, dioxane, and at least one of benzene, toluene, xylene, dichloromethane, dichloroethane, carbon tetrachloride, chloroform, and chlorobenzene.
[0022] Preferably, the material of the non-magnetic support is selected from at least one of polyesters such as polyethylene terephthalate and polyethylene-2,6 naphthalate, polyolefins such as polypropylene, celluloses such as cellulose triacetate and cellulose diacetate, vinyl resins, polyimines or polycarbonates.
[0023] A first aspect of the present invention provides a method for preparing a high recording density magnetic medium based on exchange coupling as described above, comprising the following steps:
[0024] S1, mixing the raw material components of the back coating layer, stirring evenly, to obtain a back coating layer slurry;
[0025] S2, mixing the raw material components of the second soft magnetic layer, stirring evenly, to obtain a second soft magnetic layer slurry;
[0026] S3, mixing the raw material components of the hard magnetic layer, stirring evenly, to obtain a hard magnetic layer slurry;
[0027] S4, mixing the raw material components of the first soft magnetic layer, stirring evenly, to obtain a first soft magnetic layer slurry;
[0028] S5, coating the back coating slurry on the first surface of the non-magnetic support, and drying to form a back coating;
[0029] S6, coating the second soft magnetic layer slurry on the second surface of the non-magnetic support, and sequentially passing through a magnetic orientation device and an oven for drying to form a second soft magnetic layer;
[0030] S7, coating the hard magnetic layer slurry on the second soft magnetic layer, and sequentially passing through a magnetic orientation device and an oven for drying to form a hard magnetic layer;
[0031] S8, coating the first soft magnetic layer slurry on the hard magnetic layer, sequentially passing through a magnetic orientation device and an oven for drying to form a first soft magnetic layer, and rolling up to obtain the high recording density magnetic medium based on exchange coupling.
[0032] The beneficial effects of the present invention are:
[0033] The present invention provides a high recording density magnetic medium based on exchange coupling and a preparation method thereof. The present invention adds a soft magnetic layer above and below the magnetic recording layer, so that the soft magnetic particles and the hard magnetic recording particles are at a suitable exchange coupling strength; when a reversal field is applied, the soft magnetic part rotates first, and the exchange coupling helps the hard magnetic part to reverse, so that the required reversal field can be reduced; the exchange coupling medium can maintain good thermal stability while reducing the coercive force, because the exchange coupling effect can stabilize the magnetization and increase the energy barrier, thereby preventing the magnetization state from spontaneously flipping at high temperature; on the other hand, the exchange coupling magnetic recording medium can improve the signal-to-noise ratio, reduce the read noise, and improve the reliability of stored data by optimizing the coupling strength of the soft magnetic layer and the hard magnetic layer.
[0034] The present invention optimizes the layered structure of the high recording density magnetic medium and the raw material formula of the first soft magnetic layer, the hard magnetic layer, the second soft magnetic layer and the back coating layer constituting the magnetic medium, so that the prepared product exhibits excellent comprehensive performance. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0036] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0037] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0038] The invention provides a high recording density magnetic medium based on exchange coupling, comprising a first soft magnetic layer, a hard magnetic layer, a second soft magnetic layer, a non-magnetic support body and a back coating layer which are stacked in sequence.
[0039] The present invention adds a soft magnetic layer above and below the magnetic recording layer (hard magnetic layer), so that the soft magnetic particles and the hard magnetic recording particles are at a suitable exchange coupling strength; when a reversal field is applied, the soft magnetic part rotates first, and helps the hard magnetic part to reverse through exchange coupling, which can reduce the required reversal field, reduce the required writing magnetic field, and improve the signal-to-noise ratio.
[0040] In a preferred embodiment, the raw materials for preparing the first soft magnetic layer include, by weight: 50-150 parts of soft magnetic particles, 15-80 parts of adhesive resin, 2-15 parts of abrasive, 1-10 parts of curing agent, 1-10 parts of lubricant, 1-10 parts of conductive agent, and 125-500 parts of solvent.
[0041] In a preferred embodiment, the raw materials for preparing the hard magnetic layer include, by weight: 50-150 parts of hard magnetic particles, 30-80 parts of adhesive resin, 2-15 parts of abrasive, 1-10 parts of curing agent, 1-5 parts of lubricant, 1-10 parts of conductive agent, and 150-600 parts of solvent.
[0042] In a preferred embodiment, the raw materials for preparing the second soft magnetic layer include, by weight: 50-150 parts of soft magnetic particles, 15-80 parts of adhesive resin, 2-15 parts of abrasive, 1-10 parts of curing agent, 1-10 parts of lubricant, 1-10 parts of conductive agent, and 125-500 parts of solvent.
[0043] In a preferred embodiment, the raw materials for preparing the back coating layer include, by weight: 30-80 parts of adhesive resin, 1-10 parts of curing agent, 1-10 parts of lubricant, 1-10 parts of conductive agent, and 150-600 parts of solvent.
[0044] In a preferred embodiment, the soft magnetic particles are selected from at least one of α-alumina, β-alumina, γ-alumina, θ-alumina, silicon dioxide, silicon carbide, chromium oxide, cerium oxide, α-iron oxide, goethite, corundum, silicon nitride, titanium carbide, titanium dioxide, tin oxide, magnesium oxide, tungsten oxide, zirconium oxide, boron nitride, zinc oxide, calcium carbonate, calcium sulfate, barium sulfate or molybdenum disulfide. Generally, the residual magnetic flux density is less than 10mT and the coercive force is less than 7.98kA / m (100Oe).
[0045] In a preferred embodiment, the hard magnetic particles are selected from at least one of the following materials:
[0046] Metals: Fe, Co, Ni, Alloys: Fe-Co, Fe-Ni, Fe-Al, Fe-Ni-Al, Fe-Al-P, Fe-Ni-Si-Al, Fe-Ni-Si-Al-Mn, Fe-Mn-Zn, Fe-Ni-Zn, Co-Ni, Co-P, Fe-Co-Ni, Fe-Co-Ni-Cr, Fe-Co-Ni-P, Fe-Co-B, Fe-Co-Cr-B, Mn-Bi, Mn-Al, Fe-Co-V, γ-Fe2O3, Fe3O4, Metal compounds: iron nitride, iron carbide, barium ferrite, strontium ferrite, calcium ferrite or lead ferrite.
[0047] In a preferred embodiment, the binding resin is selected from at least one of polyvinyl chloride, polyvinyl acetate, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinylidene chloride copolymer, vinyl chloride-acrylonitrile copolymer, acrylate-acrylonitrile copolymer, acrylate-vinyl chloride-vinylidene chloride copolymer, vinyl chloride-acrylonitrile copolymer, acrylate-acrylonitrile copolymer, acrylate-vinylidene chloride copolymer, methacrylate-vinylidene chloride copolymer, methacrylate-vinyl chloride copolymer, methacrylate-ethylene copolymer, polyvinyl fluoride, vinylidene chloride-acrylonitrile copolymer, acrylonitrile-butadiene copolymer, polyamide resin, polyvinyl butyral, cellulose acetate butyrate, cellulose diacetate, cellulose triacetate, cellulose propionate, nitrocellulose, styrene-butadiene copolymer, polyurethane resin, polyester resin, amino resin or synthetic rubber. The binding resin can help improve the dispersibility of the magnetic particles, prevent the agglomeration of the particles, and can also help improve the dispersibility of the abrasive.
[0048] In a preferred embodiment, the abrasive is selected from at least one of α-aluminum oxide, β-aluminum oxide, silicon carbide, chromium oxide, cerium oxide, α-iron oxide, corundum, diamond, silica rock, garnet, silicon nitride, boron nitride, molybdenum carbide, boron carbide, tungsten carbide or titanium dioxide; the abrasive can help reduce the wear, scratches and other tape damage that may occur during the operation of the magnetic recording medium and remove attachments attached to the magnetic head during the use of the magnetic recording medium.
[0049] In a preferred embodiment, the curing agent is selected from at least one of toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, naphthylene-1,5-diisocyanate, o-toluidine diisocyanate, isophorone diisocyanate or triphenylmethane triisocyanate.
[0050] In a preferred embodiment, the lubricant is selected from at least one of silicone oil, fatty acid-modified silicone oil, fluorinated silicone and other fluorinated lubricants, polyolefins, polyethylene glycol, alkyl phosphates and metal salts thereof, polyphenylene ether, fluorinated alkyl ether, lauric acid, myristic acid, palmitic acid, stearic acid, isostearic acid, arachidic acid, oleic acid, eicosanoic acid, elaidic acid, behenic acid, linoleic acid, linolenic acid, octyl stearate, isooctyl stearate, octyl myristate, isooctyl myristate, butoxyethyl stearate, butyl stearate or heptyl stearate; the lubricant can help improve the operating durability of the magnetic recording medium and inhibit head wear.
[0051] In a preferred embodiment, the conductive agent is selected from at least one of carbon black, acetylene black, carbon fiber, graphene or carbon nanotube.
[0052] A certain amount of solvent is required to prepare each coating slurry, wherein the solvent is selected from at least one of ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc., alcohol solvents such as methanol, ethanol, propanol, etc., ester solvents such as methyl acetate, ethyl acetate, butyl acetate, propyl acetate, ethyl lactate, ethylene glycol acetate, etc., ether solvents such as diethylene glycol dimethyl ether, 2-ethoxyethanol, tetrahydrofuran, dioxane, etc., aromatic hydrocarbon solvents such as benzene, toluene, xylene, etc., and halogenated hydrocarbon solvents such as dichloromethane, dichloroethane, carbon tetrachloride, chloroform, chlorobenzene, etc.
[0053] In a preferred embodiment, the material of the non-magnetic support is selected from at least one of polyesters such as polyethylene terephthalate and polyethylene-2,6-naphthalate, polyolefins such as polypropylene, celluloses such as cellulose triacetate and cellulose diacetate, vinyl resins, polyimines or polycarbonates.
[0054] The present invention also provides a method for preparing the high recording density magnetic medium based on exchange coupling as above, characterized in that it comprises the following steps:
[0055] S1, mixing the raw material components of the back coating layer, stirring evenly, to obtain a back coating layer slurry;
[0056] S2, mixing the raw material components of the second soft magnetic layer, stirring evenly, to obtain a second soft magnetic layer slurry;
[0057] S3, mixing the raw material components of the hard magnetic layer, stirring evenly, to obtain a hard magnetic layer slurry;
[0058] S4, mixing the raw material components of the first soft magnetic layer, stirring evenly, to obtain a first soft magnetic layer slurry;
[0059] S5, coating the back coating slurry on the first surface of the non-magnetic support, and drying to form a back coating;
[0060] S6, coating the second soft magnetic layer slurry on the second surface of the non-magnetic support, and sequentially passing through a magnetic orientation device and an oven for drying to form a second soft magnetic layer;
[0061] S7, coating the hard magnetic layer slurry on the second soft magnetic layer, and sequentially passing through a magnetic orientation device and an oven for drying to form a hard magnetic layer;
[0062] S8. Coating the first soft magnetic layer slurry on the hard magnetic layer, sequentially passing through a magnetic orientation device and an oven for drying to form a first soft magnetic layer, and then rolling up to obtain a high recording density magnetic medium based on exchange coupling.
[0063] The exchange coupling composite medium in the present invention utilizes the interactive coupling between the soft magnetic layer and the hard magnetic layer. When the external field is greater than the coercive force of the soft magnetic layer, the soft magnetic layer reverses first, and the magnetic moment in the soft magnetic layer couples with the adjacent magnetic moment in the hard magnetic layer, thereby reducing the coercive force required by the hard magnetic layer.
[0064] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0065] Example 1
[0066] A high recording density magnetic medium based on exchange coupling comprises a first soft magnetic layer, a hard magnetic layer, a second soft magnetic layer, a non-magnetic support body and a back coating layer which are stacked in sequence.
[0067] 1. The raw materials for the preparation of the hard magnetic layer include the following components by mass:
[0068] 100 parts by mass of hard magnetic particles, specifically barium ferrite (BaFe 12 O 19 ) Particle powder (hexagonal plate, average aspect ratio 2.8, average particle volume 1950nm 3 );
[0069] Binder resin: 42 parts by mass of a cyclohexanone solution of a vinyl chloride resin (the composition of the solution is 30% by mass of the resin and 70% by mass of cyclohexanone, a trade name of the vinyl chloride resin: MR100, manufactured by ZEON Co., Ltd.), and 18.5 parts by mass of a polyurethane resin UR8200 (manufactured by Toyobo Co., Ltd.);
[0070] 5 parts by mass of abrasive, specifically alumina powder (α-Al2O3, average particle size: 0.1 μm);
[0071] 2 parts by mass of a conductive agent, specifically carbon black (trade name: Seast TA, manufactured by Tokai Carbon C., Ltd.);
[0072] 2 parts by weight of lubricant, specifically n-butyl stearate;
[0073] 4 parts by mass of a curing agent, specifically polyisocyanate (trade name: Coronate L, manufactured by Tosoh Corporation);
[0074] Solvent: 121.3 parts by mass of methyl ethyl ketone, 121.3 parts by mass of toluene, and 60.7 parts by mass of cyclohexanone.
[0075] 2. The raw materials for preparing the first soft magnetic layer include the following components by mass:
[0076] 100 parts by mass of soft magnetic particles, specifically needle-shaped iron oxide powder (α-Fe2O3, average major axis length: 0.15 μm);
[0077] Binder resin: 44.4 parts by mass of a cyclohexanone solution of a vinyl chloride resin (the composition of the solution is 30% by mass of the resin and 70% by mass of cyclohexanone, the trade name of the vinyl chloride resin: MR100, manufactured by ZEON Co., Ltd.), and 18.5 parts by mass of a polyurethane resin UR8200 (manufactured by Toyobo Co., Ltd.);
[0078] 5 parts by mass of abrasive, specifically alumina powder (α-Al2O3, average particle size: 0.1 μm);
[0079] 10 parts by mass of a conductive agent, specifically carbon black (trade name: Seast TA, manufactured by Tokai Carbon C., Ltd.);
[0080] 2 parts by weight of lubricant, specifically n-butyl stearate;
[0081] 4 parts by mass of a curing agent, specifically polyisocyanate (trade name: Coronate L, manufactured by Tosoh Corporation);
[0082] Solvent: 108.2 parts by mass of methyl ethyl ketone, 108.2 parts by mass of toluene, and 18.5 parts by mass of cyclohexanone.
[0083] 3. The raw materials for preparing the second soft magnetic layer include the following components by mass:
[0084] 100 parts by mass of soft magnetic particles, specifically needle-shaped iron oxide powder (α-Fe2O3, average major axis length: 0.15 μm);
[0085] Binder resin: 44.4 parts by mass of a cyclohexanone solution of a vinyl chloride resin (the composition of the solution is 30% by mass of the resin and 70% by mass of cyclohexanone, the trade name of the vinyl chloride resin: MR100, manufactured by ZEON Co., Ltd.), and 18.5 parts by mass of a polyurethane resin UR8200 (manufactured by Toyobo Co., Ltd.);
[0086] 5 parts by mass of abrasive, specifically alumina powder (α-Al2O3, average particle size: 0.1 μm);
[0087] 10 parts by mass of a conductive agent, specifically carbon black (trade name: Seast TA, manufactured by Tokai Carbon C., Ltd.);
[0088] 2 parts by weight of lubricant, specifically n-butyl stearate;
[0089] 4 parts by mass of a curing agent, specifically polyisocyanate (trade name: Coronate L, manufactured by Tosoh Corporation);
[0090] Solvent: 108.2 parts by mass of methyl ethyl ketone, 108.2 parts by mass of toluene, and 18.5 parts by mass of cyclohexanone.
[0091] 4. The raw materials for preparing the back coating layer include the following components by weight:
[0092] Binder resin: 44.4 parts by mass of a cyclohexanone solution of a vinyl chloride resin (the composition of the solution is 30% by mass of the resin and 70% by mass of cyclohexanone, the trade name of the vinyl chloride resin: MR100, manufactured by ZEON Co., Ltd.), and 18.5 parts by mass of a polyurethane resin UR8200 (manufactured by Toyobo Co., Ltd.);
[0093] 5 parts by mass of abrasive, specifically alumina powder (α-Al2O3, average particle size: 0.1 μm);
[0094] 10 parts by mass of a conductive agent, specifically carbon black (trade name: Seast TA, manufactured by Tokai Carbon C., Ltd.);
[0095] 2 parts by weight of lubricant, specifically n-butyl stearate;
[0096] 4 parts by mass of a curing agent, specifically polyisocyanate (trade name: Coronate L, manufactured by Tosoh Corporation);
[0097] Solvent: 108.2 parts by mass of methyl ethyl ketone, 108.2 parts by mass of toluene, and 18.5 parts by mass of cyclohexanone.
[0098] 5. The method for preparing the high recording density magnetic medium based on exchange coupling comprises the following steps:
[0099] S1, mixing the raw material components of the back coating layer, stirring evenly, to obtain a back coating layer slurry;
[0100] S2, mixing the raw material components of the second soft magnetic layer, stirring evenly, to obtain a second soft magnetic layer slurry;
[0101] S3, mixing the raw material components of the hard magnetic layer, stirring evenly, to obtain a hard magnetic layer slurry;
[0102] S4, mixing the raw material components of the first soft magnetic layer, stirring evenly, to obtain a first soft magnetic layer slurry;
[0103] S5, coating the back coating slurry on the first surface of the non-magnetic support, and drying (90° C., 2 min) to form a back coating with a thickness of 300 nm;
[0104] S6, coating the second soft magnetic layer slurry on the second surface of the non-magnetic support, and sequentially passing through a magnetic orientation device and an oven drying (90° C., 2 min) to form a second soft magnetic layer with a thickness of 250 nm;
[0105] S7, coating the hard magnetic layer slurry on the second soft magnetic layer, and sequentially passing through a magnetic orientation device and an oven for drying (90° C., 2 min) to form a hard magnetic layer with a thickness of 50 nm;
[0106] S8. Coat the first soft magnetic layer slurry on the hard magnetic layer, and sequentially pass through a magnetic orientation device and oven drying (90°C, 2min) to form a first soft magnetic layer with a thickness of 100nm, and then roll it up to obtain a high recording density magnetic medium based on exchange coupling.
[0107] Example 2
[0108] In this example, the raw material components of the first soft magnetic layer, the second soft magnetic layer, the hard magnetic layer, and the back coating layer are the same as those in Example 1, and the non-magnetic support is also the same as that in Example 1.
[0109] In this example, the method for preparing a high recording density magnetic medium based on exchange coupling includes the following steps:
[0110] S1, mixing the raw material components of the back coating layer, stirring evenly, to obtain a back coating layer slurry;
[0111] S2, mixing the raw material components of the second soft magnetic layer, stirring evenly, to obtain a second soft magnetic layer slurry;
[0112] S3, mixing the raw material components of the hard magnetic layer, stirring evenly, to obtain a hard magnetic layer slurry;
[0113] S4, mixing the raw material components of the first soft magnetic layer, stirring evenly, to obtain a first soft magnetic layer slurry;
[0114] S5, coating the back coating slurry on the first surface of the non-magnetic support, and drying (90° C., 2 min) to form a back coating with a thickness of 300 nm;
[0115] S6, coating the second soft magnetic layer slurry on the second surface of the non-magnetic support, and sequentially passing through a magnetic orientation device and an oven drying (90° C., 2 min) to form a second soft magnetic layer with a thickness of 200 nm;
[0116] S7, coating the hard magnetic layer slurry on the second soft magnetic layer, and sequentially passing through a magnetic orientation device and an oven for drying (90° C., 2 min) to form a hard magnetic layer with a thickness of 50 nm;
[0117] S8. Coat the first soft magnetic layer slurry on the hard magnetic layer, and sequentially pass through a magnetic orientation device and oven drying (90° C., 2 min) to form a first soft magnetic layer with a thickness of 50 nm, and then roll it up to obtain the high recording density magnetic medium based on exchange coupling.
[0118] Example 3
[0119] In this example, the raw material components of the first soft magnetic layer, the second soft magnetic layer, the hard magnetic layer, and the back coating layer are the same as those in Example 1, and the non-magnetic support is also the same as that in Example 1.
[0120] In this example, the method for preparing a high recording density magnetic medium based on exchange coupling includes the following steps:
[0121] S1, mixing the raw material components of the back coating layer, stirring evenly, to obtain a back coating layer slurry;
[0122] S2, mixing the raw material components of the second soft magnetic layer, stirring evenly, to obtain a second soft magnetic layer slurry;
[0123] S3, mixing the raw material components of the hard magnetic layer, stirring evenly, to obtain a hard magnetic layer slurry;
[0124] S4, mixing the raw material components of the first soft magnetic layer, stirring evenly, to obtain a first soft magnetic layer slurry;
[0125] S5, coating the back coating slurry on the first surface of the non-magnetic support, and drying (90° C., 2 min) to form a back coating with a thickness of 300 nm;
[0126] S6, coating the second soft magnetic layer slurry on the second surface of the non-magnetic support, and sequentially passing through a magnetic orientation device and an oven drying (90° C., 2 min) to form a second soft magnetic layer with a thickness of 250 nm;
[0127] S7, coating the hard magnetic layer slurry on the second soft magnetic layer, and sequentially passing through a magnetic orientation device and an oven drying (90° C., 2 min) to form a hard magnetic layer with a thickness of 70 nm;
[0128] S8. Coat the first soft magnetic layer slurry on the hard magnetic layer, and sequentially pass through a magnetic orientation device and oven drying (90° C., 2 min) to form a first soft magnetic layer with a thickness of 100 nm, and then roll it up to obtain the high recording density magnetic medium based on exchange coupling.
[0129] Comparative Example 1
[0130] A magnetic medium comprises a soft magnetic layer, a hard magnetic layer, a non-magnetic support body and a back coating layer which are stacked in sequence.
[0131] The raw material composition of the soft magnetic layer is the same as that of the second soft magnetic layer in Example 1, the raw material composition of the hard magnetic layer and the back coating layer is the same as that in Example 1, and the non-magnetic support is also the same as that in Example 1.
[0132] The method for preparing the above-mentioned high density magnetic medium comprises the following steps:
[0133] S1, mixing the raw material components of the back coating layer, stirring evenly, to obtain a back coating layer slurry;
[0134] S2, mixing the raw material components of the soft magnetic layer, stirring evenly, to obtain a soft magnetic layer slurry;
[0135] S3, mixing the raw material components of the hard magnetic layer, stirring evenly, to obtain a hard magnetic layer slurry;
[0136] S4, coating the back coating slurry on the first surface of the non-magnetic support, and drying (90° C., 2 min) to form a back coating with a thickness of 300 nm;
[0137] S6, coating the soft magnetic layer slurry on the second surface of the non-magnetic support, and sequentially passing through a magnetic orientation device and an oven drying (90° C., 2 min) to form a soft magnetic layer with a thickness of 250 nm;
[0138] S7. Coat the hard magnetic layer slurry on the soft magnetic layer, pass it through a magnetic orientation device and oven drying (90° C., 2 min) in sequence to form a hard magnetic layer with a thickness of 70 nm, and then roll it up to obtain a magnetic medium.
[0139] The magnetic media prepared in Examples 1-3 and Comparative Example 1 were subjected to the following performance tests:
[0140] (1) Magnetic test: In the measurement of the hysteresis curve of the measurement sample, a highly sensitive vibrating sample magnetometer "VSM-P7-15 type" manufactured by Toei Industry Co., Ltd. was used. The measurement conditions were set to measurement mode: full circle, maximum magnetic field intensity: 15 kOe, magnetic field step: 40 bits, time constant of lock-in amplifier: 0.3 sec, waiting time: 1 sec, MH average: 20. The coercive force Hc, Ms, SQ were determined from the hysteresis curve. Note that for this calculation, the measurement / analysis program attached to the "VSM-P7-15 type" was used. Note that the measurement of each hysteresis curve was performed at 25°C.
[0141] (2) Roughness test: The linear roughness of the sample was tested according to ISO 4287:2010. The surface roughness of the sample was tested according to ISO 25178 using a non-contact 3D surface profiler, and the 3D surface profile of the film was observed.
[0142] (3) Signal-to-noise ratio test: First, the electromagnetic conversion characteristics (SNR) of each magnetic tape were measured in an environment of 25°C using a 1 / 2-inch tape travel device (manufactured by Mountain Engineering II, MTS Transport) equipped with a recording / reproducing head and a recording / reproducing amplifier. A ring-type head with a gap length of 0.2 μm was used as a recording head, and a GMR head with a shielding distance of 0.1 μm was used as a reproducing head. The relative speed, recording clock frequency, and recording track width were set to 6 m / s, 160 MHz, and 2.0 μm, respectively. Moreover, the SNR was calculated based on the method described in the following document.
[0143] Y.Okazaki: "An Error Rate Emulation System.", IEEE Trans.Man., 31, pp.3093-3095 (1995).
[0144] The test results are shown in Table 1 below:
[0145] Table 1
[0146] Example 1 Example 2 Example 3 Comparative Example Thickness of the first soft magnetic layer / nm 100 50 100 0 Hard magnetic layer thickness / nm 50 50 70 50 The thickness of the second soft magnetic layer / nm 250 200 250 250 Non-magnetic support thickness / μm 4.5 4.5 4.5 4.5 Back coating thickness / nm 300 300 300 300 Hc / Oe 2200 2250 2300 2500 Ms / Gs 5200 5250 5300 5200 SQ 0.68 0.68 0.68 0.66 Ra / nm 2.2 2.2 2.2 2.4 Rz / nm 37 37 37 40 SNR characteristics / dB 0.8 0.65 0.55 0.1
[0147] It can be seen from the test results in Table 1 that, compared with Comparative Example 1, the SNR characteristics of Examples 1, 2, and 3 are greatly improved, and the coercive force Hc is reduced to a certain extent. This is attributed to the alternating arrangement of the soft magnetic layer and the hard magnetic layer, which makes the adjacent magnetic moments have a coupling effect, reduces the coercive force, and improves the signal-to-noise ratio.
[0148] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A high recording density magnetic medium based on exchange coupling, characterized in that: It includes a first soft magnetic layer, a hard magnetic layer, a second soft magnetic layer, a non-magnetic support and a back coating layer which are stacked in sequence; The raw materials for preparing the first soft magnetic layer include, by weight: 50-150 parts of soft magnetic particles, 15-80 parts of adhesive resin, 2-15 parts of abrasive, 1-10 parts of curing agent, 1-10 parts of lubricant, 1-10 parts of conductive agent, and 125-500 parts of solvent.
2. The high recording density magnetic medium based on exchange coupling according to claim 1, characterized in that: The raw materials for preparing the hard magnetic layer include, by weight: 50-150 parts of hard magnetic particles, 30-80 parts of adhesive resin, 2-15 parts of abrasive, 1-10 parts of curing agent, 1-5 parts of lubricant, 1-10 parts of conductive agent, and 150-600 parts of solvent.
3. The high recording density magnetic medium based on exchange coupling according to claim 1, characterized in that: The raw materials for preparing the second soft magnetic layer include, by weight: 50-150 parts of soft magnetic particles, 15-80 parts of adhesive resin, 2-15 parts of abrasive, 1-10 parts of curing agent, 1-10 parts of lubricant, 1-10 parts of conductive agent, and 125-500 parts of solvent.
4. The high recording density magnetic medium based on exchange coupling according to claim 1, characterized in that: The raw materials for preparing the back coating layer include, by weight: 30-80 parts of adhesive resin, 1-10 parts of curing agent, 1-10 parts of lubricant, 1-10 parts of conductive agent, and 150-600 parts of solvent.
5. The high recording density magnetic medium based on exchange coupling according to claim 1 or 3, characterized in that: The soft magnetic particles are selected from at least one of α-alumina, β-alumina, γ-alumina, θ-alumina, silicon dioxide, silicon carbide, chromium oxide, cerium oxide, α-iron oxide, goethite, corundum, silicon nitride, titanium carbide, titanium dioxide, tin oxide, magnesium oxide, tungsten oxide, zirconium oxide, boron nitride, zinc oxide, calcium carbonate, calcium sulfate, barium sulfate or molybdenum disulfide.
6. The high recording density magnetic medium based on exchange coupling according to claim 2, characterized in that: The hard magnetic particles are selected from at least one of the following materials: Metals: Fe, Co, Ni, Alloys: Fe-Co, Fe-Ni, Fe-Al, Fe-Ni-Al, Fe-Al-P, Fe-Ni-Si-Al, Fe-Ni-Si-Al-Mn, Fe-Mn-Zn, Fe-Ni-Zn, Co-Ni, Co-P, Fe-Co-Ni, Fe-Co-Ni-Cr, Fe-Co-Ni-P, Fe-Co-B, Fe-Co-Cr-B, Mn-Bi, Mn-Al, Fe-Co-V, γ-Fe2O3, Fe3O4, Metal compounds: iron nitride, iron carbide, barium ferrite, strontium ferrite, calcium ferrite or lead ferrite.
7. The high recording density magnetic medium based on exchange coupling according to any one of claims 1 to 4, characterized in that: The adhesive resin is selected from at least one of polyvinyl chloride, polyvinyl acetate, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinylidene chloride copolymer, vinyl chloride-acrylonitrile copolymer, acrylate-acrylonitrile copolymer, acrylate-vinyl chloride-vinylidene chloride copolymer, vinyl chloride-acrylonitrile copolymer, acrylate-acrylonitrile copolymer, acrylate-vinylidene chloride copolymer, methacrylate-vinylidene chloride copolymer, methacrylate-vinyl chloride copolymer, methacrylate-ethylene copolymer, polyvinyl fluoride, vinylidene chloride-acrylonitrile copolymer, acrylonitrile-butadiene copolymer, polyamide resin, polyvinyl butyral, cellulose acetate butyrate, cellulose diacetate, cellulose triacetate, cellulose propionate, nitrocellulose, styrene-butadiene copolymer, polyurethane resin, polyester resin, amino resin or synthetic rubber.
8. The high recording density magnetic medium based on exchange coupling according to any one of claims 1 to 4, characterized in that: The abrasive is selected from at least one of α-aluminum oxide, β-aluminum oxide, silicon carbide, chromium oxide, cerium oxide, α-iron oxide, corundum, diamond, silica rock, garnet, silicon nitride, boron nitride, molybdenum carbide, boron carbide, tungsten carbide or titanium dioxide; The curing agent is selected from at least one of toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, naphthylene-1,5-diisocyanate, o-toluidine diisocyanate, isophorone diisocyanate or triphenylmethane triisocyanate; The lubricant is selected from at least one of silicone oil, fatty acid-modified silicone oil, fluorinated silicone and other fluorinated lubricants, polyolefins, polyethylene glycol, alkyl phosphates and metal salts thereof, polyphenylene ether, fluorinated alkyl ether, lauric acid, myristic acid, palmitic acid, stearic acid, isostearic acid, arachidic acid, oleic acid, eicosanoic acid, elaidic acid, behenic acid, linoleic acid, linolenic acid, octyl stearate, isooctyl stearate, octyl myristate, isooctyl myristate, butoxyethyl stearate, butyl stearate or heptyl stearate; The conductive agent is selected from at least one of carbon black, acetylene black, carbon fiber, graphene or carbon nanotubes; The solvent is selected from ether solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methanol, ethanol, propanol, methyl acetate, ethyl acetate, butyl acetate, propyl acetate, ethyl lactate, ethylene glycol acetate, diethylene glycol dimethyl ether, 2-ethoxyethanol, tetrahydrofuran, dioxane, and at least one of benzene, toluene, xylene, dichloromethane, dichloroethane, carbon tetrachloride, chloroform, and chlorobenzene.
9. The high recording density magnetic medium based on exchange coupling according to claim 1, characterized in that: The material of the non-magnetic support is selected from at least one of polyesters such as polyethylene terephthalate and polyethylene-2,6 naphthalate, polyolefins such as polypropylene, celluloses such as cellulose triacetate and cellulose diacetate, vinyl resins, polyimines or polycarbonates.
10. A method for preparing a high recording density magnetic medium based on exchange coupling according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing the raw material components of the back coating layer, stirring evenly, to obtain a back coating layer slurry; S2, mixing the raw material components of the second soft magnetic layer, stirring evenly, to obtain a second soft magnetic layer slurry; S3, mixing the raw material components of the hard magnetic layer, stirring evenly, to obtain a hard magnetic layer slurry; S4, mixing the raw material components of the first soft magnetic layer, stirring evenly, to obtain a first soft magnetic layer slurry; S5, coating the back coating slurry on the first surface of the non-magnetic support, and drying to form a back coating; S6, coating the second soft magnetic layer slurry on the second surface of the non-magnetic support, and sequentially passing through a magnetic orientation device and an oven for drying to form a second soft magnetic layer; S7, coating the hard magnetic layer slurry on the second soft magnetic layer, and sequentially passing through a magnetic orientation device and an oven for drying to form a hard magnetic layer; S8, coating the first soft magnetic layer slurry on the hard magnetic layer, sequentially passing through a magnetic orientation device and an oven for drying to form a first soft magnetic layer, and rolling up to obtain the high recording density magnetic medium based on exchange coupling.